Cervical and hemifacial necrotizing fasciitis. Case report - Pampin-López, Francisco (2025)
Necrotizing fasciitis is a progressively destructive infectious disease that affects the soft tissues. It is an uncommon condition associated with 10-40% mortality rates that can be as high as 80-100% if untreated. Limited information exists on this infection involving the face. We present the case of a 63-year-old male patient with no relevant past medical history who attended the emergency room with right facial and cervical edema, fever, pain, and a yellow plaque-like lesion on the periorbital area. Surgical and medical treatment were implemented. It is relevant to present this unusual clinical entity to increase awareness.